CRISPR/Cas9-Mediated Multi-Allelic Gene Targeting in Sugarcane Confers Herbicide Tolerance - Oz, Mehmet Tufan; Altpeter, Angelika; Karan, Ratna; Merotto, Aldo; Altpeter, Fredy (Frontiers in Genome Editing, 2021)
Sugarcane accounts for 80% of the sugar and 26% of the bioethanol produced globally. However, its complex highly polyploid genome (2n=100–120) impedes crop improvement. Here, we report efficient and reproducible gene targeting in sugarcane, enabling precise co-editing of multiple alleles via template mediated and homology directed repair (HDR) of DNA double strand breaks induced by the CRISPR/Cas9 programmable nuclease. Evaluation of 146 independently transformed plants from five independent experiments revealed targeted nucleotide replacement, which resulted in both targeted amino acid substitutions W574L and S653I in the acetolactate synthase (ALS) in 11 lines in addition to single, targeted amino acid substitutions W574L or S653I in 25 or 18 lines, respectively. Co-editing of up to 3 ALS copies/alleles was confirmed by Sanger sequencing of cloned long PCR amplicons, conferring herbicide tolerance. This work will enable crop improvement by modifying inferior alleles through targeted nucleotide substitutions.